2022
DOI: 10.1007/s11135-022-01554-y
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term effects of reminders on panellists’ survey participation in a probability-based panel study with a sequential mixed-mode design

Abstract: In recent panel studies, besides other methods such as sequential mixed-mode design, push-to-web method, and prepaid monetary incentives, follow-up contacts such as personalised electronic mails (e-mails) or short message service are often used to motivate nonrespondents to complete the questionnaire, increase the response rate within a limited fieldwork period, and minimise panel attrition. Since it is still unclear when and how often non-complying panellists should be reminded to take part in a survey, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Interpretation of the findings for this study should be considered within the sample's characteristics (primarily highly educated, high‐income females). This gender disparity is often observed in research participation potentially due to ease of contacting and women's greater tendency towards helping; however, for this study, women's greater interest in health and nutrition topics may have also impacted the sample's gender distribution 4,44 . Despite these privileged characteristics, the sample was still impacted by nutrition confusion and backlash.…”
Section: Discussionmentioning
confidence: 92%
“…Interpretation of the findings for this study should be considered within the sample's characteristics (primarily highly educated, high‐income females). This gender disparity is often observed in research participation potentially due to ease of contacting and women's greater tendency towards helping; however, for this study, women's greater interest in health and nutrition topics may have also impacted the sample's gender distribution 4,44 . Despite these privileged characteristics, the sample was still impacted by nutrition confusion and backlash.…”
Section: Discussionmentioning
confidence: 92%
“…Fourth, and finally, it is revealed that women are more likely to respond immediately after survey launch or in the first stages of the fieldwork period, than the male panelists. This persistent gender effect should be subjected to detailed analysis in the future (Becker, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, despite ISR's best attempts to achieve representativeness, our sample appears to be disproportionately female. This may be because women are simply more likely to participate in surveys (Becker, 2022). It may also be due in part to the demographic composition of the communities we surveyed, in which there is a notable and racialized gender imbalance created by incarceration and early death, likely exacerbated by high rates of intergenerational poverty in the neighborhoods surveyed (Lubrano, 2019).…”
Section: Discussionmentioning
confidence: 99%